Correlation Analysis Between Cardiovascular Load and Lung Function Disorders Based On FVC Values In Construction Workers - Nazhira, Fidyatul; Putri, Fadma; Fauziah, Enny; Afriani, Dini; Zahra, Siti Halwa Khoirinnisa; Lazuardi, Ghifari Theo (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Construction work environments, often characterized by exposure to dust and chemicals, pose significant risks to workers' respiratory and cardiovascular health. While much research has focused on the impact of dust on lung function, the role of cardiovascular load in contributing to these health issues remains underexplored. This study aimed to analyze the correlation between cardiovascular load (%CVL) and pulmonary function impairment based on forced vital capacity (FVC) in construction workers. Methods: This observational cross-sectional study involved 37 construction workers in Central Jakarta, selected through purposive sampling. Data were collected via spirometry and heart rate measurements before, during, and after work. Results: The results showed that 79% of respondents had restrictive disorders, while 21% had obstructive disorders. Statistical analysis revealed a significant negative correlation between %CVL and FVC values (p < 0.001; r = -0.550). These findings indicate that increased cardiovascular load is associated with decreased lung function, particularly in workers with long-term exposure to dust and extended work durations. Conclusion: Managing physical workload and controlling workplace environments are crucial to preventing pulmonary function decline in construction workers.